Notas sobre aves de la amazonia (caquetá) (1982)
During two short visits made by the author to the Araracuara region of the Colombian Amazonia, it was possible to identify and some times to photograph 66 species of birds, some of them new to the area, and others little known in relation to his ecogeographic distribution. Enfassis is made for the need to give greater importance to the sight records and new forms of identification, rather than collecting, in order to document the presence of the various species in the study areas, to adquiere more rapid information and be able to aplly this knowledge to conservation and at the same time avoid the unnecessary sacrifice of the birds.